Pengaruh Financial Literacy dan Social Media Influencer Terhadap Minat Berinvestasi di Pasar Modal Indonesia: (Studi Empiris pada Generasi Z di Jawa Timur) (Jurnal Ekonomi Bisnis dan Akuntansi, 2025)
This research aims to examine the impact of financial literacy and social media influencers on investing interest in the Indonesian capital market among Generation Z in East Java. This research examines Planned Behaviour Theory and Social Learning Theory. This research employs a quantitative methodology, using online surveys for data collection via stratified random sampling approaches including 384 respondents. Data analysis was conducted with multiple linear regression. The findings indicate that both financial literacy and social media influencers have a large and favourable impact on Generation Z's investing interest. These results endorse the use of educational and digital techniques using social media to enhance the engagement of the younger generation in the capital market.